Cholinoceptor Modulation on Nitric Oxide Regulates Prostaglandin E2 and Metalloproteinase-3 Production in Experimentally Induced Inflammation of Rat Dental Pulp - de Couto Pita, Alejandra Karina (2009)
The purpose of this study was to investigate the role of muscarinic acetylcholine receptor (mAChR) activity in the regulation of inducible nitric oxide synthase (iNOS) activity, prostaglandin E2 (PGE2), and metalloproteinase-3 (MMP-3) in experimentally induced inflammation of rat incisors dental pulp. Inflammation was induced by application of bacterial lipopolysaccharide (LPS) to the pulp. Extirpated pulp tissue samples were incubated in saline solution until the various experiments were performed. Saline-treated pulp and healthy pulp were used as controls. NOS activity was measured by the production of [U-14C]-citrulline from [U-14C]-arginine. PGE2 and MMP-3 production were evaluated by an enzyme-linked immunosorbent assay (ELISA) and cyclooxygenase (cox-1 and cox-2) messenger RNA levels were measured using a reverse-transcriptase polymerase chain reaction by coamplification of target complementary DNA with a single set of primers. The application of LPS to the pulp increased NOS activity, PGE2, and MMP-3 production associated with iNOS overactivity. Moreover, PGE2 and MMP-3 production were the result of cox-2 expression. Pilocarpine (5 × 10-11 mol/L to 5 × 10-9 mol/L), acting on mAChRs, triggered a negative effect on NOS activity, PGE2, and MMP-3 production. In control pulp, no action of pilocarpine was observed. Pulpitis changed mAChR conformation, increasing its coupling efficiency to transducing molecules that in turn activate iNOS. The capacity of pilocarpine to prevent iNOS activity, PGE2, and MMP-3 by acting on mAChR mutation induced by pulpitis might be useful therapeutically as a local treatment.